STUDENTS’ PERCEPTION OF THE USE OF ONLINE MODE TO LEARN ENGLISH ORAL COMMUNICATION SKILLS DURING COVID-19 PERIOD - Nur Shafiekah Sapan,; Loi Chek Kim, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
The Covid-19 outbreak in March 2020 forced the world to immediately change how we live, including how classes are conducted. All educational institutions must close their doors to prevent the spread of the Covid-19 virus. Teachers and students are ordered to remain at home, and the normal learning environment has to shift online. Albeit the current generations of students are no strangers to the technology used in the classroom, however, to attend a class entirely conducted online is a new situation for them. Thus, this paper aims to study students’ perceptions of using online modes in the teaching and learning process of oral communication in English. Fifty-three low-proficiency students who took Oral Communication in English at Universiti Malaysia Sabah participated in the study. A mixed-method research design was applied to the study. An open-ended questionnaire was administered to the students to elicit their perceptions on the issue. The quantitative data revealed a positive impression from the participants on teaching oral communication skills online [n=46 (87%)]. The qualitative data show that (i) interactive mode, (ii) accessibility of materials, and (iii) ability to interact with the teachers and peers without feeling shy are among the reasons why online learning is favoured.